Penatalaksanaan Fisioterapi pada Kasus Carpal Tunnel Syndrome (CTS) di Rumah Sakit Tk. II dr. Soedjono Magelang - Ii Masdayu Winakar; Rima Yunitasari; Zuyina Luklukaningsih (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a peripheral nerve disorder in the wrist caused by compression of the median nerve, which frequently affects adults and workers globally. The prevalence of CTS worldwide reaches around 5% in adults, with higher risk among women, and in Indonesia certain worker groups show relatively high risk, reaching 15%. Purpose: This study aims to describe physiotherapy management and clinical outcomes using Transcutaneous Electrical Nerve Stimulation (TENS), Ultrasound, and exercise therapy in CTS cases at dr. Soedjono Class II Hospital, Magelang. Methods: This case involved a 41‑year‑old female patient with bilateral CTS who received six physiotherapy sessions. The evaluation instruments included Visual Analogue Scale (VAS) for pain, goniometer for joint range of motion, Manual Muscle Test (MMT) for muscle strength, and Wrist Hand Disability Index (WHDI) for functional ability. Results: After six intervention sessions, changes in the form of decreased pain in all categories, resting pain T0=2 to T6=0, pressure pain T0=5 to T6=2, and motion pain T0=5–6 to T6=2. Joint range of motion increased in both wrists, the right wrist improved from T0=40°–0°–60° to T6=70°–0°–85° (sagittal) and T0=25°–0°–20° to T6=40°–0°–30° (frontal). The left wrist improved from T0=30°–0°–50° to T6=65°–0°–80° (sagittal) and T0=25°–0°–20° to T6=40°–0°–30° (frontal).  Muscle strength increased from T0=3 to T6=5 in almost all movements, except left dorsiflexion T6=4, and the WHDI score decreased frome 32 to 13, indicating reduced disability.